Use of an Expanded Polytetrafluoroethylene (ePTFE) Dura Substitute in Glioma Surgeries: A Technical Note - Rotta, José Marcus; Reis, Rodolfo Casimiro; Carvalho, Ana Lucia Mello de; Oliveira, Matheus Fernandes de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Introduction Reoperations are a common scenario among glioma patients. There is crescent evidence of its benefit in low- and high-grade gliomas. Here we discuss our experience with inert expanded polytetrafluoroethylene (ePTFE) dura substitute in glioma surgeries.Technical note We generally put the ePTFE dura substitute below the dura of the patient, even if it is intact. This membrane should be sutured in place using a tension-free technique, with 4-0 polypropylene. Expanded polytetrafluoroethylene minimizes tissue attachment and fibrosis when performing reoperation in glioma patients.Discussion Since the literature has shown benefits in survival with reoperation in glioma patients, the use of ePTFE dura substitute can improve surgical time and minimize complications in a second surgery.
Keywords: reoperation; glioma; dura substitute; surgical complication